Nigella sativa for the treatment of COVID-19: An open-label randomized controlled clinical trial - Abdulrahman E. Koshak; Emad A. Koshak; Abdullah F. Mobeireek; Mazen A. Badawi; Siraj O. Wali; Husam M. Malibary; Ali F. Atwah; Meshari M. Alhamdan; Reem A. Almalki; Tariq A. Madani (Elsevier, 2021)
Background: Effective treatment for Coronavirus Disease-2019 (COVID-19) is under intensive research. Nigella sativa oil (NSO) is a herbal medicine with antiviral and immunomodulatory activities, and has been recommended for the treatment of COVID-19. This study aimed to evaluate the efficacy of NSO treatment in patients with COVID-19. Methods: All adult patients with mild COVID-19 symptoms presented to King Abdulaziz University Hospital, Jeddah, Saudi Arabia, were recruited for an open label randomized clinical trial (RCT). They were randomly divided into control or treatment groups, with the latter receiving 500 mg NSO (MARNYS® Cuminmar) twice daily for 10 days. Symptoms were daily monitored via telecommunication. The primary outcome focused on the percentage of patients who recovered (symptom-free for 3 days) within 14-days. The trial was registered at clinicaltrials.gov (NCT04401202). Results: A total of 173 patients were enrolled for RCT. The average age was 36(±11) years, and 53 % of patients were males. The control and NSO groups included 87 and 86 patients respectively. The percentage of recovered patients in NSO group (54[62 %]) was significantly higher than that in the control group (31[36 %]; p = 0.001). The mean duration to recovery was also shorter for patients receiving NSO (10.7 ± 3.2 days) compared with the control group (12.3 ± 2.8 days); p = 0.001. Conclusions: NSO supplementation was associated with faster recovery of symptoms than usual care alone for patients with mild COVID-19 infection. These potential therapeutic benefits require further exploration with placebo-controlled, double-blinded studies.